2014
DOI: 10.4038/cmj.v59i2.7062
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue symptoms in Sri Lanka Navy personnel deployed in combat areas

Abstract: Objectives The objective was to study the prevalence of fatigue symptoms among Special Forces and regular forces military personnel deployed in combat areas and to explore factors associated with fatigue symptoms.Methods This is a cross sectional study of representative samples of Sri Lanka Navy Special Forces and regular forces deployed in combat areas continuously for at least one year. Fatigue was measured using a 12 item fatigue scale. Symptoms of common mental disorder were identified using the General He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Consisting with our findings, the naval study of Sri Lanka too saw a significant association between fatigue and PTSD and emphasized the importance of training and maintenance of good physical and mental health before combat duties (31). Trauma studies corroborate the significance of the relationship between PTSD and fatigue, attributing it to the altered emotional state and the stress-response system in general, and the hypothalamic-pituitary-adrenal (HPA) axis in particular following the exposure to trauma (32)(33)(34).…”
Section: The Psychological Behavioural and Other Associations Of Ptsdsupporting
confidence: 77%
See 1 more Smart Citation
“…Consisting with our findings, the naval study of Sri Lanka too saw a significant association between fatigue and PTSD and emphasized the importance of training and maintenance of good physical and mental health before combat duties (31). Trauma studies corroborate the significance of the relationship between PTSD and fatigue, attributing it to the altered emotional state and the stress-response system in general, and the hypothalamic-pituitary-adrenal (HPA) axis in particular following the exposure to trauma (32)(33)(34).…”
Section: The Psychological Behavioural and Other Associations Of Ptsdsupporting
confidence: 77%
“…Nevertheless, the former Army study revealed that PTSD was significantly higher in those with less education and younger age at first battle exposure (6). Strikingly, the Navy study demonstrated that personnel in the elite units compared with their counterparts in the regular units were less affected by the age at first battle exposure, and attributed to the higher degree of unit cohesion (23). International literature illuminates that, liability to PTSD increases with younger age, lower educational attainment and being unmarried, owing to the inability to cope with trauma and the vulnerability to trauma exposure (9) (24)(25)(26).…”
Section: The Socio-demographic Associations Of Ptsdmentioning
confidence: 99%
“…At the planning stage, there were no Sri Lankan studies that had assessed PIF following dengue infection. There were only two local studies that had assessed fatigue among twins (general population) and Navy officers (Ball et al, 2011;Hanwella et al, 2014). A survey among Sri Lankan physicians revealed that 77 % were reported as post-viral fatigue (Kularatne, 2005).…”
Section: Selection Cultural Adaptation and Translation Of The Chalder Fatigue Questionnairementioning
confidence: 99%